Feasibility Analysis of Establishing a Folding Dacron Mattress Business at Home Industry Puhpelem Wonogiri - Darsini Darsini; Asrori Asrori; Marwahyudi Marwahyudi (OPSI, 2022)
The establishment of home industries needs to be assessed for initial efforts to see whether the enterprise is worthy to establish or not. The study aims to learn the worthiness of the dacron bed business Pure Plembang Puhpelem, Wonogiri from non-financial and financial analyzed by the Payback Period (PP), Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), and the Internal Rate of Return (IRR). The study is qualitative-quantitative. The research subject is the home industrial bed Pure Plembang Puhpelem, Wonogiri with the dacron tree-worthy research object. Research indicates that (1) Due to market and marketing aspects, the dacron bed was more deserving because the monthly demand in each region had met its monthly target of production, (2) From the technical aspects of the dacron bed business, it was worth running, due to the location close to the existing labor and salary, (3) From the environmental aspect of the environment, the dacron is worth running because it can help the economy around the shop and is scant, and (4) From the financial aspect, with Capital Budgeting obtained PP over 5 Years 3 Months shorter than 10-year investment, NPV Rp 39,553,430 where NPV > 0, Net B/C is acquired 1.22 > 1, and IRR is 14% greater than the current interest rate (DF) at 9%. From these results, it is concluded that the financial aspect is worthy of execution.